2014
DOI: 10.2460/javma.244.8.950
|View full text |Cite
|
Sign up to set email alerts
|

Outcome for client-owned domestic rabbits undergoing limb amputation: 34 cases (2000–2009)

Abstract: Although limb amputation was tolerated by most rabbits and most owners were satisfied, complications resulted in death in 6 of 34 (18%) rabbits, and 19 of 32 (59%) developed chronic complications. Amputation in heavy rabbits or those with concurrent pododermatitis, musculoskeletal disease, or neurologic disease should be considered carefully. Because of the small sample size and retrospective nature of this study, results should be interpreted as exploratory and hypothesis generating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
4
2
Order By: Relevance
“…Limb amputation was tolerated well by the majority of animals that underwent this procedure. Apart from two patients that died postoperatively, complications (wound healing problems) were rarely observed, contrasting with the results from a previous study that reported a higher percentage of chronic complications after limb amputation in rabbits 30 . In this former study, both the median age (5.5 years) and median bodyweight (2.2 kg) of the rabbits differed distinctly from that of the rabbits in the current study, which may have led to the different complication rate.…”
Section: Discussioncontrasting
confidence: 99%
“…Limb amputation was tolerated well by the majority of animals that underwent this procedure. Apart from two patients that died postoperatively, complications (wound healing problems) were rarely observed, contrasting with the results from a previous study that reported a higher percentage of chronic complications after limb amputation in rabbits 30 . In this former study, both the median age (5.5 years) and median bodyweight (2.2 kg) of the rabbits differed distinctly from that of the rabbits in the current study, which may have led to the different complication rate.…”
Section: Discussioncontrasting
confidence: 99%
“…The long-bone fracture prevalence in the general rabbit population is likely to be higher than that presented here (1.2%) as cases may be amputated or euthanased rather than referred, and thus this study does not capture data on them. Northrup et al (2014) reported limbamputated rabbits develop post-amputation sequelae in 60% of the cases, although none were observed in the four cases undergoing limb amputation in this study, but this may reflect the relatively short follow-up time.…”
Section: Discussioncontrasting
confidence: 59%
“…Northrup et al . () reported limb‐amputated rabbits develop post‐amputation sequelae in 60% of the cases, although none were observed in the four cases undergoing limb amputation in this study, but this may reflect the relatively short follow‐up time.…”
Section: Discussionmentioning
confidence: 55%
“…Indeed, in a retrospective study of the outcome of amputation in 34 rabbits, 19 (55.9 per cent) developed chronic complications, and six (18 per cent) were euthanased because of complications. 3 As demonstrated in this case, rabbits with limb fractures can manage well with minimal intervention. If a good blood supply is maintained, rabbit bones heal quickly (within six to eight weeks).…”
mentioning
confidence: 65%
“…Furthermore, amputation surgery carries a risk of complications. Indeed, in a retrospective study of the outcome of amputation in 34 rabbits, 19 (55.9 per cent) developed chronic complications, and six (18 per cent) were euthanased because of complications 3 …”
Section: Figurementioning
confidence: 99%